Contextual Teaching and Learning (CTL) Model to Students Improve Learning Outcome at Senior High School of Model Terpadu Bojonegoro - Tamam Syaifuddin; Luthfiyah Nurlaela; Sukma Perdana P (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2021)
The purpose of the study was to analyze the improvement of student learning outcomes with the Contextual Teaching and Learning (CTL) learning model at Senior High School of Model Terpadu Bojonegoro in Civics subjects. The experimental study used a factorial design using pre-test and post-test. Collecting data using observation, documentation, and test methods. The research sample was carried out in class XI of Bojonegoro Model Terpadu Senior High School, a total of 120 students were in 4 (four) classes, each class consisted of 30 students. The technique used to check the validity in this study is triangulation and review of informants. Based on the results of research and discussion, it can be concluded that the application of the Contextual Teaching and Learning (CTL) learning model can improve Civics learning outcomes for XI grade students at Senior High School of Model Terpadu Bojonegoro. Increase in student learning outcomes by 7.08% in the second cycle.